Fertility of heifers after synchronization of estrus using GnRH, PGF2α, and progesterone (CIDR) - A.M. Richardson; B.A. Hensley; T.J. Marple; Sandra K. Johnson; Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 2002)
Our objectives were to determine fertility of heifers after estrus synchronization using PGF2αpreceded by either progesterone, GnRH, or both. Beef (n = 193) and dairy (n = 246) heifers were assigned randomly to three treatments: 1) 50 Î¼g of GnRH and a used intravaginal progesterone-releasing insert were administered on day −7, followed by 25 mg of PGF2αon day −1, and CIDR removal on day 0 (CIDR + GnRH + PGF); 2) the same as 1) but without the GnRH (CIDR + PGF); and 3) the same as 1) but without the CIDR (GnRH + PGF; modified Select Synch). Rates of estrus detection were lower in dairy than in beef heifers, and greater in heifers treated with the CIDR. In dairy heifers, conception and pregnancy rates were greatest in the CIDR + PGF treatment, followed by the CIDR + GnRH + PGF and GnRH + PGF treatments. The opposite trend was observed among treatments in beef heifers. All estrus-synchronization treatments produced acceptable estrus detection and pregnancy rates.
Keywords: Cattlemen' s Day; 2002; Kansas Agricultural Experiment Station contribution; no. 02-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 890; Beef; Estrus; Heifers; CIDR-B; Fertility